The Role of Customary Councils in Resolving Customary Land Disputes in Waropen Regency - Daniel Tanati (Faculty of Law, Universitas Pekalongan, 2025)
Disputes over customary land still occur in every region, both in the interior and in urban areas, as well as in the customary law community in Waropen Regency, customary land is still disputed to this day, both among customary law communities or between customary law communities and the Regional Government. The approach method used is empirical, namely research conducted by observing the reality that occurs in the field. The purpose of this study was to determine the role of the Customary Council in resolving customary land disputes. The results of this study revealed that the resolution of customary land disputes of the Waropen customary law community was resolved through customary law which in the Waropen language is called